Hồi cứu điều trị đau lưng cấp - Hoàng, Bảo Châu (2011)
Tác giả: Hoàng Bảo Châu, BS; Nguyễn Châu Quỳnh, BS; Trần Quốc Hiếu, BS; Nguyễn Phương Chi, BS; Ngô Thị Miến, BS -- Từ khóa: Đau lưng cấp; Điều trị; Đông y